2008
DOI: 10.1186/1471-2199-9-65
|View full text |Cite
|
Sign up to set email alerts
|

Genomic actions of 1,25-dihydroxyvitamin D3 on insulin receptor gene expression, insulin receptor number and insulin activity in the kidney, liver and adipose tissue of streptozotocin-induced diabetic rats

Abstract: Backgroundthis study set out to examine the effects of the treatment with 1,25-dihydroxyvitamin D3 (1,25D3) [150 IU/Kg (3.75 μg/Kg) one a day, for 15 days] to non-diabetic rats and in rats rendered diabetic by a single injection of streptozotocin [65 mg/kg].Resultstreatment with 1,25D3 to non-diabetic rats did not affect the biochemical parameters measured in the plasma and urine of these animals. Likewise, insulin receptor expression in the kidney, liver, or adipose tissue and insulin-stimulated glucose trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
68
1
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(81 citation statements)
references
References 51 publications
9
68
1
3
Order By: Relevance
“…The calcitriol directly activates the transcription of human Fig. 1 Comparison of the parameters in normal and type 2 diabetes subjects [35,36]. According to Ely prospective study, the baseline 25(OH)D concentration was inversely associated with glucose, IR, metabolic syndrome risk at 10 year follow up [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…The calcitriol directly activates the transcription of human Fig. 1 Comparison of the parameters in normal and type 2 diabetes subjects [35,36]. According to Ely prospective study, the baseline 25(OH)D concentration was inversely associated with glucose, IR, metabolic syndrome risk at 10 year follow up [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D is also involved in insulin regulation [3,4]. 1,25-Dihydroxyvitamin D 3 , an active form of circulating vitamin D, binds to the vitamin D receptor on pancreas beta cells and enhances insulin receptor expression, resulting in improved insulin sensitivity [27,28]. Vitamin D deficiency has also been shown to impair insulin secretion in experimental studies [3,4].…”
Section: Discussionmentioning
confidence: 99%
“…Sooy et al (52) showed that calbindin is an important regulator of insulin production, by regulating Ca concentration in the b-cell. Thirdly, s25(OH)D concentration was related to insulin sensitivity in a group of healthy non-diabetic adults (53) , and a recent animal study demonstrated that while 1,25(OH) 2 D treatment had no effect on insulin receptor expression in non-diabetic rats, it normalised the number of insulin receptors and improved insulin response to glucose transport in adipocytes in streptozotocin-induced diabetic rats, most probably by direct transcriptional activation of the rat insulin receptor gene (54) .…”
Section: Glucose and Insulin Metabolism And Type 2 Diabetesmentioning
confidence: 99%